A “história afro-brasileira” nos currículos da formação de professores na UEPA - Silva, Jerônimo Cavalcante Dantas da (Universidade Federal do Tocantins, 2023)
This report has aims to analyze the curricula of undergraduate courses in Pedagogy, History and Physics, offered by the University of the State of Pará (UEPA), campus of Conceição do Araguaia. This theoretical foundation is housed in the interdisciplinary field of curriculum studies, adding here questions related to structural racism with applicability in the core of education. With this, the scientific knowledge mobilized helps us to think of Afro-Brazilian history as something procedural and essentially interdisciplinary. The methodology is of the documentary type with a qualitative approach, because we are treating the Pedagogical Political Project (PPP) of the mentioned degrees as a document, with a view to understanding the construction of the syllabi of the analyzed disciplines. The curricular components that, in some way, interface with studies on Afro-descendant culture and society were selected. The data revealed little curricular projection regarding the discussion of Afro-Brazilian history, which proved to be without space in the curricular guidelines. This was aggravated by the fact that the bibliographic references in the menus were out of date and outside the scope of Afro-Brazilian public policies. This, in turn, reveals degrees in curricular transition, but still with a strong traditional.